Gheetto at the center of the world - Mathews, Gordon (Chicago University of Chicago Press, 2011)
Ghetto at the Center of the World shows us, a trip to Chungking Mansions reveals a far less glamorous side of globalization. A world away from the gleaming headquarters of multinational corporations, Chungking Mansions is emblematic of the way globalization actually works for most of the world$1 (Bs people. s